Carbapenem-Resistant Organisms Isolated in Surgical Site Infections in Benin: A Public Health Problem - Yehouenou, Carine Laurence; Soleimani, Reza; Kpangon, Arsène A.; Simon, Anne; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; Dalleur, Olivia (My University, 2022)
Abstract: An alarming worldwide increase in antimicrobial resistance is complicating the management of surgical site infections (SSIs), especially in low-middle income countries. The main objective of this study was to describe the pattern of carbapenem-resistant bacteria in hospitalized patients and to highlight the challenge of their detection in Benin. We collected pus samples from patients suspected to have SSIs in hospitals. After bacterial identification by MALDI-TOF mass spectrometry, antimicrobial susceptibility was performed according to the Kirby–Bauer method. Carbapenemresistant strains were characterized using, successively, the Modified Hodge Test (MHT), the RESIST-5 O.K.N.V.I: a multiplex lateral flow and finally the polymerase chain reaction. Six isolates were resistant to three tested carbapenems and almost all antibiotics we tested but remained susceptible to amikacin. Four (66.7%) of them harbored some ESBL genes (blaCTX-M-1 and blaTEM-1). The MHT was positive for Carbapenems but not for Pseudomonas aeruginosa and Acinetobacter baumannii. As surgical antimicrobial prophylaxis, five of the six patients received ceftriaxone. The following carbapenems genes were identified: bla OXA-48(33.3%, n = 2), blaNDM (33.3%, n = 2) and blaVIM (33.3%, n = 2). These findings indicate a need for local and national antimicrobial resistance surveillance and the strengthening of antimicrobial stewardship programs in the country.
Keywords: carbapenem-resistant organisms; OXA-48; NDM; VIM; surgical site infections; Benin